ELR-based patches and hydrogels to treat ischaemic diseases.
The current absence of an efficient drug delivery system for ischaemic diseases is plaguing therapy performance. Elastin-like recombinamer (ELR) patch and gel developed under the ANGIOMATTRAIN (Development of Biomaterial-based Delivery Systems for Ischaemic Conditions-An Integrated Pan-European Approach) project, along with a novel medical device to deliver them to the clinical target, are hoped to result in shorter hospital stays and recovery times for patients.